2003
DOI: 10.3354/meps255135
|View full text |Cite
|
Sign up to set email alerts
|

Trophic importance of Laminaria hyperborea to kelp forest consumers and the importance of bacterial degradation to food quality

Abstract: The nutritional value of kelp Laminaria hyperborea (Gunn.) Foslie and the importance of bacterial degradation in making kelp available to consumers were tested by no-choice feeding experiments. Fresh and dead kelp material degraded in situ was sampled. In the laboratory, fresh kelp was degraded for 3, 14 and 44 d by kelp associated bacterial communities under aerobic and anaerobic conditions. The fresh and degraded kelp products were fed to the kelp associated amphipods Jassa falcata, Lembos websteri, Ampithoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 61 publications
3
117
5
Order By: Relevance
“…N-limitation). Norderhaug et al (2003) showed that amphipods from Northern Norway only fed on kelps after the algal tissue had gone through a significant bacterial degradation, i.e. N-enrichment.…”
Section: Herbivores In Kongsfjordenmentioning
confidence: 99%
“…N-limitation). Norderhaug et al (2003) showed that amphipods from Northern Norway only fed on kelps after the algal tissue had gone through a significant bacterial degradation, i.e. N-enrichment.…”
Section: Herbivores In Kongsfjordenmentioning
confidence: 99%
“…Fish aggregate over the kelp forest, in between the kelps and on the sea floor (FossĂ„ 1995;Norderhaug et al 2005). Fresh kelp is not the preferred food source of most grazers (see Christie & Rueness 1998;Norderhaug et al 2003), but many species obtain their food from kelpproduced carbon (Fredriksen 2003), and the majority of the fauna feed on particulate organic matter from kelp enriched by microorganisms rather than grazing directly on kelp and epiphytic algae Norderhaug 2004). Fish predation, migration and space limitations contribute to limit the amount of small grazers Norderhaug et al 2005.…”
Section: System Stability and Shifts Between Kelp Forests And Sea Urcmentioning
confidence: 99%
“…Secondly, amphipods are most abundant in the early fall, a period when there is little phytoplankton in the sea (Dale et al 1999). Recent studies have shown that some of the most common amphipod species in the kelp forest like Jassa falcata, Ampithoe rubricata, Lembos websteri and Gammarus locusta can grow and survive on kelp as long as the C:N ratio and phlorotannin content is reduced by bacterial degradation (Norderhaug et al 2003).…”
Section: Carbon Sourcesmentioning
confidence: 99%